2017
DOI: 10.1504/ijrapidm.2017.082152
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and fatigue failure of 3D printed parts with continuous fibre reinforcement

Abstract: This paper introduces a design methodology used to integrate continuous fibre reinforcement into AM polymer parts with the aim of improving their mechanical properties. Tensile and low cycle fatigue testing of reinforced parts is carried out for a range of load conditions and strain rates Physical testing showed that it was possible to improve the strength of parts by 400% and cycles to failure by 42,800% with the addition of 4% carbon by weight. Logarithmic load/cycle relationships were found also samples sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It has been shown that printed parts obtained with this method generally present less porosity than the previous process. However, potential limitations can be anticipated due in part to both the design and poor infiltration of the fiber in the polymer [ 2 , 105 ].…”
Section: Technology Landscape and Future Trendsmentioning
confidence: 99%
“…It has been shown that printed parts obtained with this method generally present less porosity than the previous process. However, potential limitations can be anticipated due in part to both the design and poor infiltration of the fiber in the polymer [ 2 , 105 ].…”
Section: Technology Landscape and Future Trendsmentioning
confidence: 99%
“…Defects specific to the FFF process (high void content, poor interlayer bonding, and inhomogeneous fibers distribution) have a significant impact on the strength to interlaminar shear and on the breaking behavior of 3D-printed specimens [ 23 , 24 , 25 , 26 , 27 ]. However, researchers have studied and significantly improved the mechanical performance of composites reinforced with continuous fibers, using various types of tests as compression [ 28 , 29 ], tensile [ 30 , 31 , 32 ], bending [ 33 , 34 , 35 ], fatigue [ 36 , 37 ], and impact [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Londhe et al (2016) presented the effect of coatings on Jute/epoxy which reduces its moisture absorption. In additive manufacturing, the mechanical properties are improved by introducing a design methodology which was discussed by Brooks et al (2017) in integrate continuous fibre reinforcement in polymer parts. Sushmita et al (2016) investigated experimental free and forced vibration of hybrid composite plates.…”
Section: Introductionmentioning
confidence: 99%